Pericarp polypeptides and SRAP markers associated with fruit quality traits in an interespecific tomato backcross - Pereira Da Costa, Javier Hernán (2014)
The aim of this study was to detect polypeptides and genomic regions associated with fruit quality traits in a backcross generation using as parent the Argentinean cultivated tomato Caimanta of Solanum lycopersicum and the wild accession LA722 of S. pimpinellifolium. We tested two types of molecular marker: polypeptide profile (at two ripening stages, mature green and red ripe) and SRAP (sequence-related amplified polymorphism). A polypeptide of 45 kDa present in the wild parents at the mature green stage was associated with larger fruit and long shelf life. Some amplification fragments from SRAP markers were associated with more than one quality trait such as fruit color, firmness, titratable acidity, and fruit soluble solids content. This study demonstrated for the first time the usefulness of the polypeptide profiles of pericarp and SRAP markers in finding associations with quality fruit traits in a tomato backcross generation